Ruehssia sumiderensis (Apocynaceae), a new species from Chiapas state, Mexico - Lozada-Pérez, Lucio; Ramírez-Marcial, Neptalí; González-Martínez, Sar Adrián (Phytotaxa, 2020)
It is herein presented Ruehssia sumiderensis as a new species known only in the Cañón del Sumidero National Park, in Chiapas, Mexico. It is illustrated with a line drawing, live images and SEM photographs of the gynostegium and pollinarium. Morphological and molecular evidence with plastid data (trnL intron and trnL-F intergenic spacer) confirms its position in Ruehssia, a recently proposed genus that includes American Marsdenieae species. It is similar to Marsdenia laxiflora and M. pinetorum due to the basally rounded or truncate leaves, rotate corolla without callous cushions in the sinuses. Two new combinations are also made in Ruehssia, for M. laxiflora and M. pinetorum.